Epidemiological profile and temporal trend of schistosomiasis cases in Northeastern Brazil, 2008-2017 (Research, Society and Development, 2022)
The objective was to describe the epidemiological profile and temporal trend of cases of schistosomiasis in Northeast Brazil from 2008 to 2017. This is a quantitative and descriptive ecological study on cases of schistosomiasis in Northeast Brazil from 2008 to 2017. Data were collected from the Notifiable Diseases Information System (SINAN), stratified by year of first symptom, state of residence, sex and age group. The information was arranged using descriptive statistics: mean, standard deviation, minimum and maximum. The incidence rate (IR) was calculated and used to estimate trends, performed using Prais-Winsten regression. In total, 18,101 cases of schistosomiasis were recorded. It was evident, throughout the time series, high incidence rates in Pernambuco with an average of 6.83 cases per 100,000 inhabitants (SD=7.96) and in Bahia with 5.59/100,000 (SD=3.25). In this scenario, the Annual Percentage Change (APC) of IR in the Northeast was -14.99% per year. In the state of Rio Grande do Norte, there was a downward trend (APC=-13.68%), as well as in Pernambuco (APC=-23%) and Bahia (APC=-10.55%). The highest occurrences of cases were observed in males with 9,890 cases and in the age group of 20-29 years with 6,874 cases. In the present study, it was possible to observe a high number of cases of schistosomiasis in the Northeast region. The temporal trend was of decrease in the states of Rio Grande do Norte, Pernambuco, Bahia and in the Northeast, while the others were stationary.